Effectiveness of microsurgical palatal tonsillectomy in patients with oropharyngeal cancer and metastases of squamous cell carcinoma into the cervical lymph nodes without identified primary lesion - M. I. Sokolova; D. M. Rostovtsev; A. O. Guz (Опухоли головы и шеи)
Introduction. Metastasis without an identified primary lesion is an unresolved and complex problem in clinical oncology. The issue of the necessity of primary lesion identification remains controversial. According to some studies, detection of the primary tumor potentially reduces the dose of radiation therapy and therefore prevents development of toxic reactions that reduce the quality of life of the patient, and in some cases completely eliminates the need for adjuvant therapy. Widespread development and application of robotic, microsurgical, and laser transoral techniques make it possible to verify latent oropharyngeal cancer. The detection of overexpression of p16 protein in metastatic affected lymph nodes may indicate the association of this pathology with human papillomavirus.Aim. To investigate the efficacy of microsurgical palatal tonsillectomy (using a surgical microscope) in diagnosis and treatment of occult oropharyngeal cancer in patients with cervical lymph node metastases of undetected primary site, determine the frequency of expression of the surrogate marker of human papillomavirus – protein p16.Materials and methods. The study was based on the results of diagnosing 82 patients with cervical lymph node metastases of undetected primary site. The inclusion criteria were morphologically verified cervical lymph node metastases of squamous cell carcinoma, absence of a primary tumour after a standard clinical examination. 10 patients underwent palatal tonsillectomy using a surgical microscope and cervical lymph node dissection based on the results of clinical examination and instrumental diagnostics.Results. The use of microsurgical palatal tonsillectomy in patients with metastases of squamous cell carcinoma in the cervical lymph nodes without identified primary lesion allowed to diagnose cancer of the palatine tonsil in 12.1 % of cases, cancer of this location associated with human papilloma virus in 70 % of cases.Conclusion. Microsurgical palatal tonsillectomy using a surgical microscope allowed us to not only verify occult palatine tonsil cancer, but also to establish accurate diagnosis and stage of the disease with subsequent determination of the scope of adjuvant therapy.